AGRICULTURAL LAND CONVERSION INTO RICE RICE FIELD IN PALM PLANTATION KENAGARIAN TIGO KOTO SILUNGKANG PALEMBAYAN DISTRICT DISTRICT AGAM - Silvia, Voni - (STKIP PGRI Sumbar, 2014)
This research on the background of the background by the number of people in Kenagarian Tigo Koto subdistrictSilungkang Palembayan Agam district rice paddy land conversion to oil palm plantations. This study aims todetermine the data or information and analyze the data in depth about how and why farmers to convert agriculturalland to paddy rice in the palm Plantations Kenagarian Tigo Koto subdistrict Silungkang Palembayan Agam district.The research is a qualitative study using snowball sampling technique. Furthermore, the data collected throughinterview, observation and documentation, after the data were obtained, the data was analyzed through imagingtechniques words. The results of the research field as follows: First, the way the management of rice farmers is morecomplex and takes a long while oil management simpler and in need of a short time. Second, the reason for farmersto convert agricultural land into oil palm plantations of lowland rice is divided into two, namely internal and externalfactors. Internal factors can be seen from the conditions of employment and income levels. Where people interestedin switching function because the work is more promising than paddy rice farming, in addition to any income earnedit more. While external factors cause farmers to convert agricultural land into oil palm plantation rice paddy views ofthe risk of failure in the rice paddy fields affected by poor water and pests, while the oil is more susceptible to pestsand irrigation systems. For the cost of production is not comparable with the results of lowland rice production in theevent of crop failure, while the cost of oil production is proportional to the output.